Sexism in french textbooks Alter Ego Plus B1 - Febrian, Nurraffi; Ekowati, Sri Harini; Lustyantie, Ninuk (Franconesia, 2022)
The purpose of this research is to determine the gender bias found in the textbook Alter Ego Plus B1. The types of gender bias based on Fakih's classification are subordination, marginalization, stereotypes, violence, and multiple workloads. The approach used in this research is qualitative with content analysis method. Data was collected using observing and note-taking techniques. The data analysis technique used in this study refers to the theory of Miles and Huberman, in which there are 3 processes: (1) data reduction, (2) data presentation, and (3) drawing conclusions. In the process of data reduction, research collects text or sentences, and pictures or illustrations that contain gender bias meanings. The next stage is the data presented in the form of data analysis tables, and classified according to the type of gender bias contained. To end the research, the final stage is drawing conclusions, by concluding the types of gender bias found in the Alter Ego Plus B1 textbook, and how gender bias is represented according to Fakih's theory. The results showed that there were around 33 types of gender bias, of which there were 6 subordination, 10 marginalization, 12 stereotypes, 0 violence, and 5 double workloads according to Fakih's theory. Based on the results of the research that has been presented, it is expected that students of the French language study program can know and understand the meaning of gender and the types of gender bias that exist in current cultural conditions, especially in textbooks.